ARABIC AS A MEDIUM FOR REPRESENTING LOCAL CULTURAL VALUES: A SPEECH ACT ANALYSIS OF MAHASANTRI AT MA'HAD AL-JAMIAH TUANKU IMAM BONJOL PADANG BASED ON SUMBANG DUO BALEH - Kenny Andika; Yasmadi Yasmadi; Rahmawati Rahmawati; Habibullah Ahmadi (Lingeduca: Journal of Language and Education Studies, 2026)
This study aims to analyze the representation of Sumbang Duo values in the Arabic speech of female mahasantriwithin a local wisdom-based Arabic language learning program at Ma'had Al-Jami'ah UIN Imam Bonjol Padang. The study employed a descriptive qualitative approach, using 60 Arabic utterances as the data, which were analyzed based on John Searle’s Speech Act Theory. The analysis focused on identifying speech act types, illocutionary functions, and the representation of Sumbang Duo Baleh values. The findings reveal that directive speech acts predominated in the mahasantri's utterances, with prohibitive illocutionary acts emerging as the most frequently employed form. The representation of Sumbang Duo Baleh values was classified into five cultural themes: communication ethics, personal conduct ethics, appearance ethics, social relationship ethics, and responsibility ethics. These findings demonstrate that Arabic language learning not only fosters linguistic competence but also serves as a medium for representing local cultural values through communicative practices. This study contributes to the growing body of research on local wisdom-based Arabic language learning by demonstrating how cultural values are realized through speech acts in authentic language use.